Quality of Shrimps Landed in Different Fish Landing Centers of Tuticorin, Tamil Nadu - G., Jeyasekaran; M., Michael Antony; R., Jeya Shakila (Fishery Technology, 2025)
A comparative study on the quality of shrimps landed in four fish landing centers (Therespuram, Punnakayal, Tuticorin fishing harbour and Tharuvaikulam) of Tuticorin region was investigated. The shrimps collected from the landing centers scored an overall sensory score of > 7.0 out of 10.0. Most of the shrimps (80%) collected had TMA-N content more than 5 mg%. TVB-N content of only 40% of the shrimps exceeded the limit of 30 mg%. Indole was higher than 3.1|jg/100g in all the samples, but within 25 tig/100g. The total bacterial load of 75% of shrimps were within the acceptable level of 105 cfu/g. Total and faecal coliforms and E. coli counts of shrimps of Therespuram were quite high. Staphylococcus aureus counts were high in shrimps of Punnakayal. Vibrio parahaemolyticus counts were almost similar in all the samples. V. cholerae, Salmonellae and Listeria monocytogenes were absent in all the shrimp samples examined. The shrimps landed in Tharuvaikulam had a better quality when compared to the shrimps landed in the other three fish landing centers.